2021
DOI: 10.3389/fpubh.2020.633888
|View full text |Cite
|
Sign up to set email alerts
|

Student Volunteering as a Solution for Undergraduate Health Professions Education: Lessons From the COVID-19 Pandemic

Abstract: In response to the COVID-19 pandemic, many medical universities worldwide, including the Poznan University of Medical Sciences, launched student volunteering projects (SVPs). We examined our student volunteers' perceptions on the conditions, safety, costs and benefits of their participation in the SVP. Using this information, we attempted to assess the viability of SVPs as a solution for health professions education during and after the pandemic. The main research tool was a questionnaire on students' percepti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
52
1
10

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(69 citation statements)
references
References 30 publications
6
52
1
10
Order By: Relevance
“…A similar observation has been made in other countries, where traditional volunteering is being replaced by its modern form (Brooks, 2002;Fényes & Pusztai, 2012;Handy et al, 2010;Holdsworth, 2010;Hustinx, 2001;Hustinx & Lammertyn, 2003;Rehberg, 2005;Voicu & Voicu, 2009). Table 3 The impact of religion on students' motivations to volunteer Statistically significant differences are written in boldface Motivations To experience the adventure and to tell my future kids that I was a part of it At the same time, this study shows that similar to other countries, future healthcare professionals in Poland expressed a strong interest in active participation during the current health care emergency (Chawłowska et al, 2021;Drexler et al, 2020;Gallagher & Schleyer, 2020;Gouda et al, 2020;Miller et al, 2020;Soled et al, 2020;Thomson & Lovegrove, 2020). Furthermore, although students' religiosity was not a significant predictor of volunteering during the COVID-19 outbreak, it influenced their motivations to join the fight against the pandemic.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…A similar observation has been made in other countries, where traditional volunteering is being replaced by its modern form (Brooks, 2002;Fényes & Pusztai, 2012;Handy et al, 2010;Holdsworth, 2010;Hustinx, 2001;Hustinx & Lammertyn, 2003;Rehberg, 2005;Voicu & Voicu, 2009). Table 3 The impact of religion on students' motivations to volunteer Statistically significant differences are written in boldface Motivations To experience the adventure and to tell my future kids that I was a part of it At the same time, this study shows that similar to other countries, future healthcare professionals in Poland expressed a strong interest in active participation during the current health care emergency (Chawłowska et al, 2021;Drexler et al, 2020;Gallagher & Schleyer, 2020;Gouda et al, 2020;Miller et al, 2020;Soled et al, 2020;Thomson & Lovegrove, 2020). Furthermore, although students' religiosity was not a significant predictor of volunteering during the COVID-19 outbreak, it influenced their motivations to join the fight against the pandemic.…”
Section: Discussionmentioning
confidence: 77%
“…Unsurprisingly, religion has been defined as an important predictor of volunteering, and it is now well documented that both religious beliefs and practices influence volunteers' motivations. Moreover, while research shows that the importance of helping others is more common among religious people, it has also been found that members of religious congregations volunteer more This is important, especially during the current health crisis caused by the COVID-19 outbreak, because volunteering constitutes the chief example of civic consciousness and responsibility (Chawłowska et al, 2021;Drexler et al, 2020;Gallagher & Schleyer, 2020;Gouda et al, 2020;Miller et al, 2020;Soled et al, 2020;Thomson & Lovegrove, 2020). This is especially so in countries like Poland, which struggle with the problem of a decreasing number of health professionals (Eurostat, 2020a), or in countries that have experienced care staff shortages during the COVID-19 pandemic (Rasmussen et al, 2020;Stokes, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The current study revealed the perceptions of final-year pre-registered nursing students volunteering as frontline healthcare workers during the COVID-19 pandemic, focusing on the factors influencing their decision to volunteer, the role of their professional identity as nurses to volunteer, and strategies to improve future volunteering uptake and processes. While the exploration of healthcare students’ perceptions and experiences of volunteering during the COVID-19 pandemic is not new [ 8 , 9 , 14 , 15 ], this study contributes to the current literature by demonstrating what worked well, and the efforts to improve future operational processes when recruiting students as frontline healthcare workers to ease manpower constraints.…”
Section: Discussionmentioning
confidence: 99%
“…An increasing number of workers succumbed to coronavirus infections, and there was a problem with workforce shortage in hospitals. To prevent the healthcare system from being overwhelmed, Slovakia, as well as other European countries, decided to involve medical students as volunteers or to stage their practical learning in hospitals [ 3 ].…”
Section: Introductionmentioning
confidence: 99%